Uncertainties of a near 90 GHz sea ice concentration retrieval algorithm - Beitsch, Alexander (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2014)
Passive microwave remote sensing of sea ice concentrations has proven to be the backbone to understand the polar sea ice covers, which are key elements in the global climate system. In over 30 years of remote sensing of sea ice, several retrieval algorithms have been developed using brightness temperature measurements for the investigation of the sea ice covered area by means of the sea ice concentration. Knowledge about the uncertainty of the retrieved ice concentrations is essential to quantify observed trends in sea ice area against the background of natural variability and for the assimilation of sea ice concentrations into numerical weather prediction models. Changes in surface emissivity and variations in atmospheric parameters, like water vapour and cloud cover, are known to have an influence on the accuracy of the retrieved ice concentration. Additionally, the quality of retrieved sea ice concentrations depends on an appropriate choice of the tie-points, which are defned as typical brightness temperatures measured over the surfaces involved. We investigate uncertainties of a near 90 GHz retrieval algorithm, called the ARTIST Sea Ice algorithm (ASI), by intercomparison with other sea ice concentration data sets. First, we compare ASI and sea ice concentrations retrieved from other retrieval algorithms with visual ship-based observation of the sea ice concentration around Antarctica. After adapting ASI to the new Advanced Microwave Scanning Radiometer 2 (AMSR2) that recently started to provide brightness temperature measurements, we compare the new ASI sea ice concentrations with the Comiso Bootstrap (BST) retrieval, which performed best in the first comparison, and with satellite optical imagery and ice surface temperatures in the Arctic. ASI shows a higher agreement with the other data than BST. Both comparisons show that ASI performs well for different satellite sensors and in different hemispheres. In addition, we present the influence of changing surface emissivities and variations due to changing ...